(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Stem cell transplantation in combination with administration of bioactive compounds has shown promising results in treating myocardial infraction (MI). In the current study, we investigated the effect of combining mesenchymal stem cells (MSCs) transplantation with heparin into the infarcted heart rabbits. For this purpose, 35 male New Zealand white rabbits were randomly divided into five groups: sham, MI, MI+ MSCs, MI+ heparin and MI+MSCs+ heparin. MI was induced by 30 min ligation of the left anterior descending coronary artery. The animals of MSCs and MSCs +heparin groups were injected cell culture containing MSCs intramyocardially into the infarct area. Functional parameters of the left ventricle by echocardiography, serum levels of VEGF by enzyme-linked immunosorbent assay, size of fibrotic area by Masson’s trichrome staining, evaluation of morphology by Haematoxylin-Eosin and capillary density alkaline phosphatase staining were compared between groups. Ejection fraction, fractional shortening and levels of VEGF significantly improved in MSCs and MSCs + heparin group (P<0.05). The fibrotic area was significantly reduced (p=0.009) in MSC + heparin treated animals in comparison with MSCs. Number of live cells and angiogenesis were increased significantly in MSCs + heparin groups in comparison with MSCs (p< 0.05). Although injection of MSCs significantly restored normal function of fibrotic area, we found that administration of heparin combined with MSCs to infarcted heart of animals could have better effects on LV functional parameters in fibrosis area and resulted in superior therapeutic outcome in enhancing neovascularization and improving cardiac fibrosis